Effect of Thinning Intensity on Fiber Morphology and Crystallinity of Poplar - Bai-Xiang Cui; Jun-Long Liu; Nan Zhou; Wen-Ping Wu; Xue-Hai Tang; Chang-Jun Ding; Shuangyan Zhang; Chuan-Gui Wang (BioResources)
Thinning silviculture is a forestry measure that can improve forest ecosystems and stand structure. Thinning can impact the properties and quality of poplar wood. This study investigated the effects of three different thinning intensities on the fiber morphology and crystallinity of poplar wood, providing a theoretical basis for the cultivation and rational processing of poplar plantations. The results indicated significant differences in the proportion of wet heartwood area among different thinning intensities. With increased thinning intensity, the wet heartwood area proportion rose, while it decreased with wood height under the same thinning intensity. Fiber length increased with thinning intensity, reaching a 16% increase at 50% thinning, as well as with sampling height. Fiber width grew with thinning intensity, initially widening, and then narrowing with height. Cell wall thickness first increased and then decreased with thinning intensity, peaking at 50% thinning. The fiber length-width ratio increased with thinning intensity and initially increased then decreased with height. The fiber-diameter-cavity ratio also increased with thinning intensity and height. Crystallinity showed a trend of first increasing and then decreasing with tree height, peaking at breast height, and it was higher in normal wood than in wet heartwood under the same thinning intensity.